Synthesis and anticonvulsive activity of tricyclic analogs of benzhydrylurea - Bakibaev A. A. Abdigali Abdimanapovich; Gorshkova V. K.; Tignibidina L. G.; Saratikov A. S.; Pustovoitov A. V.; Khlebnikov A. I. Andrey Ivanovich (1995, 1995)
Title screen